Homeschooling Myths Revisited (International Journal of Innovative Research in Engineering & Management, 2021)
More parents are opting to homeschool  their children rather of sending them to public or private  schools. Find out more about the homeschooling  movement and what it entails when parents teach their  children at home. Homeschooling is a rising trend in which  parents teach their kids at homes instead of transferring  kids to a traditional government or private school. Parents  homeschooling for a variety of reasons, including  dissatisfaction with educational options, cultural or  educational differences, and the notion that children do not  develop properly in the traditional school system. In the  1970s, a number of well-known authors and scholars,  including John Holt, Dorothy Moore, and Raymond  Moore, started writing concerning educational change, the  homeschooling movement took off. They advocated for  homeschooling as a viable educational choice. In the  Western States, the general public sees and writes about  homeschooling children who win or place highly in  international vocabulary and geography competitions;  homeschooling kids who enrol in prestigious colleges; and  how schools are now seeking and accepting homeschooled  kids. They look at the results of many studies that compare  homeschoolers' academic achievement to that of their  public school counterparts. Moreover, during the last  several years, the movement has been gradually  expanding.
Keywords: Child Education; Education in India; Home Education; Home Schooling; Home Schooled Kids